Статеві особливості міжпівкулевої асиметрії викликаних потенціалів кори головного мозку у правшів та лівшів - Качинська, Тетяна; Kachynska, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Дослідження проведено на 80 особах різної статі, поділених за типом сенсо-моторної асиметрії на правшів та лівшів. Незалежно від статі та типу сенсо-моторної асиметрії, за швидкістю сприйняття та обробки зорової інформації зафіксовано домінування лівої півкулі, а за значеннями амплітуд − вищі активаційні процеси в зонах правої півкулі. 80 subjects, 17−18 years old, sorted into groups of left- and right-handers, both males and females took part in the study. The brain cortex evoked potentials study was held under conditions of rhythmic photosti¬mulation (100 stimuli total). Brain cortex visual EP computer study was carried using amplitude-time brain cortex EP features analysis. The subjects were characterized by specific feature – the dominance of left hemisphere in visual information speed perception and further processing, independently of sex and manual asymmetry type. The higher activation processes during visual information perception and processing, according to evoked potentials components amplitude values, were observed in the areas of right hemisphere.
Gender Peculiarities of Visual Evoked Potential Interhemisphere Asymmetry of Right- and Left-Handers
Keywords: викликані потенціали; амплітуда; пікова латентність; правші; лівші; evoked potentials; amplitude; peak latency; right-handers; left-handers